Una aproximación a las experiencias de intervención psicosocial con hombres y nuevas masculinidades en Quito de octubre del año 2015 a febrero del 2016 - Heredia Vargas, Diego Fernando (2016)
Speak of masculinity, it is to investigate the patriarchal constructions of being a man and how these behaviors are bound together with gender violence, considering the existence of programs that work with men, where the main goal it’s to generate moments for reflection in order to eradicate gender violence in the City of Quito, this establish that there is a chance to rebuild the concept of men. The advantage of getting a vision from the directors of these experiences is to know their view about intervention, patriarchy, gender violence and masculinity. Providing a dynamic work with questions and personal experiences of all people who have had the necessity of questioned themselves about men practices and their relationship with the environment taught by Institutions, archetypes assigned by society even before birth.